Correlation of cardiotocography with combined APGAR scores and diagnostic performance of umbilical cord parameters in predicting low combined APGAR scores - A prospective Cohort study - Soumyashree Paikaray; Saubhagya Kumar Jena; Deepthy Balakrishnan; Pankaj Kumar Mohanty (Elsevier, 2024)
Objectives: Combined Apgar score includes utilization of interventions such as Continuous positive airway pressure, Oxygen, Mask and Bag ventilation, I ntubation and ventilation, Ne onatal chest compression, Drugs, and newborn assessment. It has been proposed as a substitute for conventional Apgar score which is the gold standard for evaluating newborns right after birth but is impacted by medical interventions and preterm. Combined Apgar scores were examined to check for correlation with CTG tracing and umbilical cord blood parameters which gives an objective assessment of fetal hypoxia, in response to the demand for a more accurate tool for evaluating the neonate and to be used for medico-legal purposes. The study's objectives were to (1) determine the association of combined Apgar scores with suspicious and pathological CTG (2) the association of umbilical cord parameters with low combined Apgar scores and the diagnostic performance of these parameters in predicting low combined Apgar scores. Study design: A prospective observational cohort study was conducted in a tertiary care center in East India. 2350 consecutive laboring mothers who had completed 34 weeks of gestation underwent cardiotocography according to institutional protocol and those with suspicious and pathological CTG who delivered within 1 h of abnormal CTG were recruited. Arterial blood was analyzed and the newborn was evaluated immediately after delivery with a combined Apgar scoring system Results: Of the 2350 women, 50.7 % and 49.3 %, respectively, exhibited suspicious and abnormal CTG tracings. CTG was reported to have low diagnostic accuracy and specificity, with a sensitivity of 66.7 % and 88.9 %, respectively, in detecting combined Apgar at 1 and 5 min. The combined Apgar score at five minutes showed a strong association with acidosis. There was a statistically significant correlation between low combined Apgar and excess lactate and base at one and five minutes. With 100 % sensitivity and 95 % specificity, high lactate levels > 4.1 mM/L were found to predict newborn encephalopathy. Conclusion: Umbilical cord blood parameters were found to be correlated with low combined Apgar scores. Combined Apgar scores may be a more useful tool for neonatal assessment and long-term morbidity of newborns. Additional research is required to determine whether it can take the role of conventional Apgar scores in clinical practice.